Realizing Child-Friendly Schools: The Role of Kampus Mengajar 8 Students as Agents of Change in Anti-Bullying Education at SMP Barunawati 3 - Dewi, Adinda Kharisma; Miftakh, Fauzi (ALACRITY : Journal of Education, 2025)
This study aims to analyze students' understanding of bullying which includes film screening and role playing in increasing students' awareness and knowledge about bullying issues. The method used is qualitative descriptive research with data collection through questionnaires, direct observation during education sessions, and observation of role playing results. The data obtained are grouped based on the category of students' understanding before and after education, the effectiveness of film screening, and student involvement in role playing. The results showed an 85% increase in students' understanding of the types, impacts, and prevention of bullying after participating in education. Students showed an increase in awareness reflected in changes in their attitudes and reactions to the material taught, especially in understanding the importance of preventing bullying in the school environment. In conclusion, the educational method applied has proven effective in increasing students' understanding and awareness of bullying, and can be a useful model to be applied in schools in efforts to prevent bullying. This study contributes to the development of educational methods that are more interactive and touch the emotional aspects of students in overcoming bullying problems in the school environment.